Factors affecting capital expenditure in provincial governments in Indonesia - Ningrum, Dwi Asih Setya; Fitriasuri, Fitriasuri; Mellita, Dina; Sartika, Dewi (Jurnal Ekonomi, 2024)
This study aims to determine the influence of regional original revenue, general allocation funds, specific allocation funds, and excess of budget calculations on capital expenditures in provincial governments in Indonesia in 2020-2022. The population in this study covers 34 provinces in Indonesia. This study used purposive sampling method so that 34 provinces were obtained as research samples. The data used in this research is secondary data in the form of Budget Realization Reports for provincial governments in Indonesia. This study uses multiple regression analysis. The results of this study indicate that simultaneously local revenue, general allocation funds, specific allocation funds, and excess budget calculations have a positive effect on capital expenditures. Partially, local revenue, general allocation funds and the remainder of the budget calculation have a positive effect on capital expenditures.